Validated HPTLC method for standardization of an ayurvedic powdered formulation-Panchsakar churna - Puspendra Kumar,; Shivesh Jha,; Durgawati Patel,; Sanjar Alam, (International Journal of Phytomedicine, 2014)
Objective: Panchsakar Churna is a marketed ayurvedic powdered formulation containing Cassia angustifolia and Terminalia chebula as the main ingredients. Present study aims to standardize Panchsakar Churna based upon chromatographic and spectral studies. Methods: This study developed an efficient and reliable high performance thin layer chromatographic method for quantification of Sennoside B and Gallic acid in Panchsakar Churna. The developed method was validated for linearity, accuracy, precision, sensitivity and purity. Results: Linearity of peak area was tested in the range 0.310-3.100µg/spot (r=0.9835) and 0.200-2.000 µg/spot (r=0.9929), Accuracy was assessed with recovery and the recoveries were 99.909-100.330 % and 99.690-100.562 % (n=3 for each sample), Precision were 0.257-2.580 and 0.425-2.201, sensitivity was determined with respect to limit of detection and limit of quantification, limit of detection were 73.7634 ng/spot and 50.1556 ng/spot, while limit of quantification were 245.8781ng/spot and 167.1853ng/spot, purity of the spot were 0.9984-0.9999 (r) and 0.9977-0.9998 (r) respectively for Sennoside B and Gallic acid. Conclusion: Sennoside B and Gallic acid can be used as possible marker compound for standardization of Panchsakar Churna.